PEMBUATAN PROGRAM APLIKASI SISTEM INVENTORI TOKO OBAT - Novita Novita; Dali S. Naga; Ririen Setyarini (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
The purpose of this study is to design a drug store inventory system that can provide accurate information to help monitoring the drug storing. The computerized system facilitates the provision of reports for owner of the drug store to assist in decision-making to improve the quality of performance of the drug store. In designing system, System Development Life Cycle (SDLC) method with a waterfall approach is chosen. Application development is done by using Microsoft Visual Basic .Net 2008 programming language, Microsoft SQL Server 2012 database and Crystal Reports reporting tools.